Dzieje jednej faktury. Glosa do przypisu, czyli Central Park Heinricha Himmlera - Jerzy Giebułtowski (Zagłada Żydów)
On 16 February 1943 Heinrich Himmler gave the order to demolish the Warsaw ghetto and deport its remaining Jewish population, all this in an attempt to complete the process of the destruction of Jews. The liquidated ghetto territory was to be turned into a park, half the size of New York’s Central Park. The invoice for the demolition and cultivation of rubber root (one of Himmler’s ‘exotic projects’) was made out to the Ministry of Finance by the SS Main Economic and Administrative Office despite the failure of those two enterprises. It remains unknown whether the enormous amount due (150 million RM, that is, the equivalent of a minimum 500–600 million in today’s dollars) was paid in full out or what happened with the valuables and other material salvaged during the demolition. The text discusses the course of the demolition and deportation ordered by Himmler and the history of the invoice.